OPTIMALISASI BIAYA DAN WAKTU PELAKSANAAN PEKERJAAN PERANCAH MENGGUNAKAN SCAFFOLDING PADA BANGUNAN BERTINGKAT DENGAN SISTEM ZONING - Santoso, Suselo Utoyo, Armin Naibaho, Edy (Prokons: Jurnal Teknik Sipil, 2015)
On the implementation of the scaffolding work in a large and typical structures, the work area usually is distributed into several areas or work zones due to the limited area for mobilization of material and equipment, work schedule, structure form, limited resources and so on. The distribution of the different areas or zones in the typical structure will affect the circulation of the equipment removal of the scaffolding .The review was carried out by simulating the time various working methods using zones in 1 floor and 8 different floors. The zoning was of 6 zones, 3 zones, and 1 zones for one floor with various completion of 10 work days, 7 work days, and 5 work days. Work schedule was made based on each model. With reference to the work schedule, calculations, cost and time maximization of scaffolding was carried out. Data analysis process?s were (1) material and tool analysis, (2) job cost analysis, and (3) unit price analysis. The calculations result in an effective and efficient method is by employing 3 zones withim 7 work days for each floor. So it is for the entire 8 floor. With the implementation cost as many as IDR 42,203,210 for 1 floor and IDR 327,113,217 for 8 floors.Keywords: maximization, scaffolding, zone